2023
DOI: 10.1038/s41467-023-38234-w
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between cardiorespiratory fitness and type 2 diabetes

Abstract: Higher cardiorespiratory fitness is associated with lower risk of type 2 diabetes. However, the causality of this relationship and the biological mechanisms that underlie it are unclear. Here, we examine genetic determinants of cardiorespiratory fitness in 450k European-ancestry individuals in UK Biobank, by leveraging the genetic overlap between fitness measured by an exercise test and resting heart rate. We identified 160 fitness-associated loci which we validated in an independent cohort, the Fenland study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…While there is substantial evidence on how galectin-1 modulates inflammation, studies are needed to further elucidate the direct effects of galectin-1 in healthy muscle physiology [40]. High intensity training increases CRF, which in turn is causally associated with lower risk of T2D in genetic studies [41][42][43]. As galectin-1 is a proposed biomarker in T2D, future studies should examine the potential biomarkers capabilities of serum galectin-1 in exercise interventions in patients with T2D.…”
Section: Plos Onementioning
confidence: 99%
“…While there is substantial evidence on how galectin-1 modulates inflammation, studies are needed to further elucidate the direct effects of galectin-1 in healthy muscle physiology [40]. High intensity training increases CRF, which in turn is causally associated with lower risk of T2D in genetic studies [41][42][43]. As galectin-1 is a proposed biomarker in T2D, future studies should examine the potential biomarkers capabilities of serum galectin-1 in exercise interventions in patients with T2D.…”
Section: Plos Onementioning
confidence: 99%
“…The innovation of our approach is contextualized by a rich history of approaches targeting CRF prediction to ease clinical translation. Indeed, previous work to develop nonexercise prediction models of CRF has spanned physical activity questionnaires [51][52][53][54][55][56][57][58][59][60] , resting heartrate 53,58,60 , BMI/body composition [51][52][53][54][55][56][57][58][59][60][61][62][63] , genetics 64 , proteomics 16 , metabolomics 13 and activity monitor data [61][62][63]65 . However, most previous studies have been conducted in healthy or trained individuals and lack a demonstration of strong relations with to multisystem clinical outcomes.…”
Section: Articlementioning
confidence: 99%
“…Moreover, reducing glucose entry into β-cells for aerobic metabolism directly reduces ROS production and attenuates oxidative stress [176]. A recent large cohort study showed that appropriate exercise increases cardiorespiratory fitness, and that a higher cardiorespiratory fitness reduces T2DM risk [177]. The American College of Sports Medicine updated the Consensus Statement on exercise in patients with T2DM in 2022 [178].…”
Section: Diet-and Exercise-based Therapymentioning
confidence: 99%